Minimally invasive surgical treatment of bladder pain syndrome in women - Yu. A. Ignashov; I. V. Kuzmin; M. N. Slesarevskaya; S. H. Al-Shukri (Вестник хирургии имени И.И. Грекова)
The OBJECTIVE was to study the efficiency and tolerability of minimally invasive surgical methods of treatment in women with bladder pain syndrome (BPS).METHODS AND MATERIALS. 110 women with a confirmed diagnosis of BPS participated in this study, their age was 19 to 78 years (mean age (44.7±3.3) years). The treatment was divided into 3 consecutive stages. The first line of treatment included behavioral and pharmacotherapy, the second line was hydrodistension of the bladder and the third line of treatment was intravesical botulinum therapy (intravesical injections of botulinum toxin type A at 20 points of the bladder wall, 5 U in each pint, total dose was 100 U). The method of performing bladder hydrodistension consisted of the maximum filling of the urinary bladder at a pressure of 100 cm of water column, exposure time was 2 min, the procedure was repeated twice with an interval of several minutes. The examination of the patients was carried out before treatment and one month after the start of treatment measures at each stage of treatment. Patients were transferred to the next line of therapy if the previous stage was ineffective. Improvement of the patient’s quality of life by at least 1 point according to the QoL questionnaire was used as a criterion for the effectiveness of treatment.RESULTS. Conservative treatment was effective only in 21 (19.1 %) of 110 treated patients. The remaining 89 patients underwent bladder hydrodistension, the positive results of that were in 46 (51.6 %) patients. Botulinum therapy was effective in 41 (95.3 %) of 43 treated patients with BPS refractory to previous lines of treatment. The effectiveness of minimally invasive methods of treatment was increased in patients with a lower initial bladder capacity, higher stage of cystoscopic changes in the bladder wall and severity of clinical manifestations of the disease. The tolerability of the treatment was satisfactory.CONCLUSION. The results of the study showed high efficiency and good tolerability of minimally invasive methods of treatment in women with BPS.